Penyelidikan Motif Penulis dan Pesan Teologis Melalui Analisis Komposisi Narasi Kitab Hakim-Hakim 6-8 - Adiatma, Daniel Lindung; Pattinaja, Aska Aprilano (Jurnal Teologi dan Pelayanan Kerusso, 2024)
This research presents a combination of two approaches, historical criticism and narrative criticism, in analyzing the motifs of the author of the book of Judges through the narrative of Israel's deliverance by Gideon. The debate among Old Testament scholars regarding historicity and theological historiography has divided opinions into two camps that are difficult to reconcile. Although each approach has its own strengths and weaknesses, the combination of both can enrich an approach to the analysis of a narrative text. Judges 6-8 are rarely interpreted using both of these approaches. For historical critical interpreters, emphasis on historicity and the documentary sources forming the narrative is crucial. However, they often overlook the literary devices that bind these historical fragments. On the other hand, narrative criticism, which focuses on literary devices, tends to trap interpreters in the subjectivity of interpretation. Some interpretations with ethical, moral, and practical theological nuances have also made leaps too far without considering the author's motifs. Through the combination of historical criticism and narrative criticism, this research has identified the author's motifs as fundamental theological values that can serve as a foundation for developing theology. This research has found that the author of the book encourages the generations of Israel to maintain their identity through theological messages about God's interaction in Israel's history during the era of Gideon.